Comparison of subsequent pregnancy outcomes after surgery for adnexal masses performed in the first and second trimester of pregnancy. Issue 3 (11th December 2019) - Zou, Gen; Xu, Ping; Zhu, Libo; Ding, Shaojie; Zhang, Xinmei
Abstract: Objective: To determine whether surgery for adnexal masses in the first trimester of pregnancy affects subsequent pregnancy outcomes compared to surgery in the second trimester. Methods: Data were retrospectively reviewed from women who underwent adnexal mass surgery before 26 weeks of gestation at a university hospital between July 2008 and June 2018. Women who underwent surgery in the first trimester were classified as group 1 (n=78) and those in the second trimester were classified as group 2 (n=48). Information on clinical characteristics and pregnancy outcomes was obtained from medical records and follow‐up interviews and compared between two groups. Results: There were no differences in age, parity, mass size, laparoscopy, and operation time between the two groups. A total of 98 cases were confirmed as ovarian torsion, including 72 cases in group 1 and 26 cases in group 2. Accordingly, adnexectomy was performed more often in group 1 ( P =0.002). No significant differences concerning the rate of abortion, preterm birth, or cesarean delivery were found. Conclusion: Surgery for adnexal masses performed in the first trimester is almost as safe as that in the second trimester. Surgery should be performed for women with a complex adnexal mass in the first trimester to avoid unfavorable complications. Abstract : Surgery for adnexal masses in the first trimester does not affect subsequent pregnancy outcomes compared to surgery in the second trimester.